Volume-Based F-18 FDG PET/CT Imaging Markers Provide Supplemental Prognostic Information to Histologic Grading in Patients With High-Grade Bone or Soft Tissue Sarcoma. Issue 51 (December 2015) - Andersen, Kim Francis; Fuglo, Hanna Maria; Rasmussen, Sine Hvid; Petersen, Michael Mork; Loft, Annika
Abstract : Abstract: The aim of the study is to assess the prognostic value of different volume-based calculations of tumor metabolic activity in the initial assessment of patients with high-grade bone sarcomas (BS) and soft tissue sarcomas (STS) using F-18 FDG PET/CT. A single-site, retrospective study from 2002 to 2012 including 92 patients with histologically verified high-grade BS (N = 37) or STS (N = 55). All patients underwent a pretreatment F-18 FDG PET/CT scan. Clinical data were registered. Measurements of the accuracy of metabolic tumor volume with a preset threshold of 40% of the maximum standardized uptake value of primary tumor (MTV40% ) and total lesion glycolysis (TLG) as prognostic variables and identification of optimal discriminating cut-off values were performed through ROC curve analysis. Patients were grouped according to the cut-off values. All deaths were considered an event in survival analysis. Kaplan–Meier survival estimates and log-rank test were used to compare the degree of equality of survival distributions. Prognostic variables with related hazard ratios (HR) were assessed using Cox proportional hazards regression analysis. Forty-one of 92 patients died during follow-up (45%; 12 BS and 29 STS). Average survival for included patients was 6.5 years (95% CI 5.8–7.3 years) and probability of 5-year survival was 52%. There was a high-significant accuracy of TLG and MTV40% as prognostic variables when looking on all patients and during subgroup analysis. AUCs were higher for TLG than for MTV40% . TLG above optimal cut-off value was the only variable which was independently prognostic for survival throughout multivariate regression analysis of all included patients ( P = 0.01, HR 4.78 [95% CI 1.45–15.87]) and subgroup analysis (BS: P = 0.04, HR 11.11 [95% CI 1.09–111.11]; STS: P < 0.05, HR 3.37 [95% CI 1.02–11.11]). No significant results were demonstrated for MTV40% . Volume-based F-18 FDG PET/CT imaging markers in terms of pretreatment estimation of TLG provide supplemental prognostic information to histologic grading, with significant independent properties for prediction of overall survival in patients with high-grade BS or STS.